Legal Consequences for Children Born from Surrogacy Contracts - Ida Bagus Abhimantara (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Abstract Technological advance in medical field, especially concerning non-natural pregnancy, such as surrogacy that is present as a solution for couples experiencing infertility as outlined in contract can certainly have legal consequences. This study addresses legal consequences of a child born from surrogacy contract. Research method used in this paper is doctrinal legal research. The legal consequences of children born from surrogate mothers’ agreement lie in the legal standing for them and the right of inheritance they own. Reviewed from Indonesian legislation, a child born from surrogacy contract is a legal child of the surrogate mother and is not a legal child of his biological parents; in the case of inheritance rights, if a child is categorized as a legal child, he/she may inherit the full property of the surrogate mother and her husband, whereas if the child is classified as a child outside of marriage, she/he has only a cognate relationship with the mother who gave him/her birth. Keywords: inheriting rights; legal consequences; legal status; surrogacy contract